Endothelial-specific Crif1 deletion induces BBB maturation and disruption via the alteration of actin dynamics by impaired mitochondrial respiration. Issue 7 (July 2020) - Lee, Min Joung; Jang, Yunseon; Han, Jeongsu; Kim, Soo J; Ju, Xianshu; Lee, Yu Lim; Cui, Jianchen; Zhu, Jiebo; Ryu, Min Jeong; Choi, Song-Yi; Chung, Woosuk; Heo, Chaejeong; et al.
Cerebral endothelial cells (ECs) require junctional proteins to maintain blood–brain barrier (BBB) integrity, restricting toxic substances and controlling peripheral immune cells with a higher concentration of mitochondria than ECs of peripheral capillaries. The mechanism underlying BBB disruption by defective mitochondrial oxidative phosphorylation (OxPhos) is unclear in a mitochondria-related gene-targeted animal model. To assess the role of EC mitochondrial OxPhos function in the maintenance of the BBB, we developed an EC-specific CR6-interactin factor1 ( Crif1 ) deletion mouse. We clearly observed defects in motor behavior, uncompacted myelin and leukocyte infiltration caused by BBB maturation and disruption in this mice. Furthermore, we investigated the alteration in the actin cytoskeleton, which interacts with junctional proteins to support BBB integrity. Loss of Crif1 led to reorganization of the actin cytoskeleton and a decrease in tight junction-associated protein expression through an ATP production defect in vitro and in vivo. Based on these results, we suggest that mitochondrial OxPhos is important for the maturation and maintenance of BBB integrity by supplying ATP to cerebral ECs.